Buddy games : spring awakening [videorecording (DVD)] - Duhamel, Josh, 1972-; McKinley, Gabe; Thoele, Rachael; Roday, James; Goodwin, Ginnifer; Dillon, Kevin; Swardson, Nick; Playfair, Dylan, 1992-; Bakkedahl, Dan, 1969- (Paramount Home Entertainment, 2023)
Faced with their biggest challenge yet, the gang sets out to honor a lost friend only to find themselves in the middle of where it all began, Spring Break, where they learn their old school ways of partying hardly compete with today's generation.